PENGARUH KONFLIK KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT POS INDONESIA (Persero) BENGKULU 38000 - Endi Pratama Erwandari; Anggri Puspita Sari (Management Insight: Jurnal Ilmiah Manajemen, 2018)
This research aims to know the effect of work conflicts and working pressure toward employees’ performance of PT.Pos Indonesia (Persero) Bengkulu 38000. This research was an explanatory research by using quantitative research. Sample of this research was all of the population of the PT.Pos Indonesia (Persero) Bengkulu 38000 employee with total sample was 103 employee. To know the validity of the data, the researcher used validity and reliability of instrument. Meanwhile, to analyze the data, the researcher used double linier regression. Based on the result of analysis data, the researcher found that 1) concurrently work conflicts and working pressure give significant positive effect toward the employees’ performance of PT.Pos Indonesia (Persero) Bengkulu. 2) Partially work conflicts give significant positive effect toward the employees’ performance of PT.Pos Indonesia (Persero) Bengkulu. 3) Partially working pressure give significant positive effect toward the employees’ performance of PT.Pos Indonesia (Persero) Bengkulu.